2021
DOI: 10.3390/molecules26133971
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizing Antivirals

Abstract: Antiviral action of various photosensitizers is already summarized in several comprehensive reviews, and various mechanisms have been proposed for it. However, a critical consideration of the matter of the area is complicated, since the exact mechanisms are very difficult to explore and clarify, and most publications are of an empirical and “phenomenological” nature, reporting a dependence of the antiviral action on illumination, or a correlation of activity with the photophysical properties of the substances.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 124 publications
0
21
0
1
Order By: Relevance
“…For many years, photosensitizers have mainly been used as antitumor therapy, for which many photosensitizers have already been proven to be clinically safe, and some are currently approved for use in humans ( 35 ). Although reports on the PDI of viruses go back to 1960, where it was shown that some photosensitive dyes, such as methylene blue, had an antiviral effect, it is only in the last decades that photosensitizers have gained considerable interest as antimicrobial (bacteria, fungi, and viruses) agents due to their strong antimicrobial effects and low toxicity in normal tissue ( 36 , 37 ). A major advantage of those molecules is that, due to their direct damaging effect on the microorganism, they are insensitive to the onset of resistance of the microorganism against the compound, the latter being a major problem in today’s research on antivirals and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, photosensitizers have mainly been used as antitumor therapy, for which many photosensitizers have already been proven to be clinically safe, and some are currently approved for use in humans ( 35 ). Although reports on the PDI of viruses go back to 1960, where it was shown that some photosensitive dyes, such as methylene blue, had an antiviral effect, it is only in the last decades that photosensitizers have gained considerable interest as antimicrobial (bacteria, fungi, and viruses) agents due to their strong antimicrobial effects and low toxicity in normal tissue ( 36 , 37 ). A major advantage of those molecules is that, due to their direct damaging effect on the microorganism, they are insensitive to the onset of resistance of the microorganism against the compound, the latter being a major problem in today’s research on antivirals and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, new chemicals and materials can wonderfully assist the rapid detection and preliminary screening of such pathogens. For example, we can develop new chemical reagents, novel materials, and clinical diagnostic kits for infectious diseases such as COVID-19, viral hepatitis, tuberculosis, AIDS, hemorrhagic fever, dengue fever, influenza, and diarrhea; we could also design high-throughput diagnostic chemical reagents or materials and supporting equipment accordingly that can simultaneously detect multiple pathogens and discrepancy in drug resistance [20] , [37] ; chemically modified environmental-friendly metals like copper or silver nanoparticles, and even polymer-metal nanocomposites could be prepared for antibacterial or antiviral applications in sterilization [26] , [38] , [39] , [40] ; novel chemical formulations, materials, sprays, gels, and other relevant products with photo [41] , [42] , [43] , sound, magnetic [44] , [45] and thermal responsiveness might be developed; specifically designed disinfectants and biosafety cleaning systems could be applied for the open environment as well as confined space especially with personnel on-site.…”
Section: Possible Application Of Biosafety Chemistry and Biosafety Materialsmentioning
confidence: 99%
“…[49] . In short, it is imperative to apply new chemical subtances and materials to develop light, electric, sound, magnetic, and thermo-responsive disinfectants that are colorless, odorless, non-toxic, non-corrosive, environment-friendly, and degradable with no heavy metal residuals [41] , [42] , [43] .…”
Section: Possible Application Of Biosafety Chemistry and Biosafety Materialsmentioning
confidence: 99%
“…Near infrared light (NIR) or far-red light with a wavelength between 620 nm and 850 nm is able to penetrate deeper into tissue, which makes it the best phototherapeutic window. Effective light sources include lasers, light-emitting diodes (LEDs), and filtered incandescent light [ 15 , 16 ]. A review by Wiech et al, 2019, provides extensive information on the activity of different classes of photosensitizer on various viruses [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A review by Wiech et al, 2019, provides extensive information on the activity of different classes of photosensitizer on various viruses [ 17 ]. Most of the dangerous, persistent, or emerging viruses are enveloped viruses [ 16 ]. Studies have shown that these viruses are particularly sensitive to PDT because their lipid envelope is easily oxidized [ 16 ].…”
Section: Introductionmentioning
confidence: 99%